تقييم الأثر على تصورات الطالبات المعلمات الذين يخضعون للأسلوب التعليمي متعددة الوسائط في الدراسات الإسلامية في السياق السعودي: دراسة نوعية للمساعدات البصرية/الرسوم البيانية - Alzarah, layla (مجلة جامعة الملك عبدالعزيز: العلوم التربوية والنفسية, 2024)
Abstract Objective: This qualitative study aims to explore the perceptions of female student teachers in their final year, majoring in the Islamic Studies discipline at King Faisal University. The focus is on their experiences when practicing teaching through visuals, infographics, videos, or documentaries in various lessons of the Islamic studies curriculum, employing a multimodal instructional approach from a cognitive load perspective. The study derives common thematic strands related to individual identity, Saudi national identity, and Saudi citizenship through a literature review, with emphasis on Vision 2030. Methods: The analysis of perceptions is based on structured interviews with five questions addressing these themes, followed by analysis using MAXQDA. Results: A preliminary analysis of the qualitative data reveals a heightened sense of these identities among student teachers, despite some conflicting perceptions regarding the use of infographics, visuals, and videos. The research suggests an increased awareness among student teachers regarding their Islamic national identities and Saudi Islamic citizenship, particularly in the context of rapid policy transformations within the Kingdom. Conclusions: There is a notable alignment between the objectives of Vision 2030 and the teaching approach utilizing visuals and infographics. However, the study also identifies a need for further research on other tools employed in this instructional methodology.